Cultivate Africa-Dialog: Women in Agriculture Session - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
The Cultivate-Africa Dialog #1 has been designed as a response to the Joint Ministerial Declaration and Action Agenda from the Joint Virtual Meeting of the African Ministers Responsible for Agriculture, Trade and Finance on the Impact of Covid-19 on Food and Nutrition Security in Africa held in April and in July 2020. It specifically aims to spur action that addresses the objective the ministers highlighted for “short- and medium-term interventions needed to ensure food availability and access as well as long term productivity.” With this is mind, the specific objectives of the Women in Agriculture Track were: • Highlight why supporting and investing in young women is critical for solving global hunger amidst major crisis like climate change and COVID-19 • Showcase success stories involving young women (and men); lessons learnt and how these can be scaled up or inform broader ongoing initiatives • Build linkages and partnerships to promote resilient all-inclusive African agriculture and food system